Analisis Penggunaan TikTok sebagai Media Marketing Perspektif Kaidah Fikih Dar’ul Mafāsid Muqaddamun `alā Jalbi al-Masāliḥ: Analysis of the Use of TikTok as a Marketing Media from the Perspective of the Islamic Legal Maxim of Dar’ul Mafāsid Muqaddamun `alā Jalbi al-Masāliḥ - Qonitah Amatullah Zain; Muhamad Arifin; Imron Rosyadi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyze the use of Tiktok as a marketing medium by using the perspective of the fiqh rule Dar'ul Mafāsid Muqaddamun `alā Jalbi al-Masāliḥ. This research includes qualitative research and literature study using a descriptive approach to the characteristics of the Tiktok application. The results of the research found that TikTok has mafsadah and maslahah that should be considered for use for a Muslim in general and business people in particular. On a macro scale, namely looking at the scope of pluralistic society and the realities of use in general, this rule can be applied in punishing the use of the Tiktok application in general and specifically as a marketing medium. The mafsadah arising from the use of Tiktok intersects a lot with the values of maqashid al-syari`ah, especially in terms of protecting the soul, religion and honor. So for the sake of long-term benefit it is necessary to apply this rule, namely preventing these mafsadah by reducing, regulating or eliminating the Tiktok application altogether. As for the micro-scale use of each individual, this rule cannot be applied because the mafsadah caused from a personal point of view and use is still not strong enough to be the reason for the urgency of prevention because some individuals have reasons for greater mafsadah if they close the use of Tiktok at once, such as the reason for fulfilling basic life needs that can harm them if not fulfilled. So this rule cannot be applied because one of the conditions for applying this rule is that the prevention of the first mafsadah does not cause greater mafsadah afterwards. The results of this study are expected to provide another point of view in terms of fiqh, as well as add broader insight into mafsadat and maslahat to business people who use the Tiktok application as a marketing medium.